2021
DOI: 10.1002/jpen.2231
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with intestinal failure from an intestinal rehabilitation unit in a country without home parenteral nutrition

Abstract: Objective: For the first time, we reported experiences with an intestinal rehabilitation unit (IRU) from a country without home parenteral nutrition (HPN). Methods:We included patients with a diagnosis of intestinal failure (IF) since the establishment of our IRU from February 2018 to February 2020. We further report on our protocols for management of enterocutaneous fistulas (ECFs), short-bowel syndrome (SBS), chronic intestinal pseudo-obstruction and motility disorders.Results: Among a total of 349 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In 2022, an intestinal rehabilitation unit in Shiraz, Iran, reported their initial experience treating adult GF patients [45,46 ▪ ]. This report was equally important to the Argentina report because no center has established an organized intestinal rehabilitation program in the Middle East, where home PN services are severely limited [44].…”
Section: Multidisciplinary Approach With Surgical Gut Rehabiliationmentioning
confidence: 99%
“…In 2022, an intestinal rehabilitation unit in Shiraz, Iran, reported their initial experience treating adult GF patients [45,46 ▪ ]. This report was equally important to the Argentina report because no center has established an organized intestinal rehabilitation program in the Middle East, where home PN services are severely limited [44].…”
Section: Multidisciplinary Approach With Surgical Gut Rehabiliationmentioning
confidence: 99%
“…In these instances, surgery will be planned at an earlier timepoint. In countries where facilities for HPN do exist, time of surgery should be delayed to a minimum of six months up to one year, as mentioned above [30 ▪ ,31 ▪ ]. Multiple episodes of fistula-related complications may also warrant earlier surgery (for example recurrent CLABSI or destructive inflammation of the skin).…”
Section: Timing Of Autologous Gut Reconstruction/enteroatmospheric Fi...mentioning
confidence: 99%
“…To achieve the best outcome, the operation should be performed in a tertiary health center where adequate experience with this type of surgery exists [36 ▪ ]. A study by one of the authors, Nikoupour et al [30 ▪ ] showed that establishing an intestinal rehabilitation unit (in a country without HPN availability) drastically reduced mortality (42% vs. 6.2%).…”
Section: Preoperative Management and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Acutely ill and metabolically unstable IF patients who have survived a complicated abdominal surgery are cared for in intestinal rehabilitation units (IRU) by a multidisciplinary team (MDT) including surgeons, pharmacists, nutritionists and various other specialists [ 9 ]. The MDT designs essential PN and hydration, manages fistulae, open abdomen, PN complications and infections until the patient becomes independent of inpatient PN or is prepared for further abdominal operations including autologous intestinal reconstruction (AGIR) or intestinal transplantation [ 10 12 ]. AGIR refers to various surgical techniques to enhance intestinal absorptive mucosa in order to minimize dysmotility and the need for intestinal transplantation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%